(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3gPg CHhGH GdCSeGA , HGH aYd (B( (3HaJM GdaGA (B) s
(3BNQgG (B:s
(3hGWeCf hCWHCf HeYfi , hCbSCf EPG cHQ hGcHCf Ci EfbHV Je cJGH GdgeR , hHJeGeg Je OjhGf GdCOH s
(3GdLRA GdCNjQ ef fSNI CNQis
(3HBNQg JbQjX ddcJGH dfThGf Hf SYjO GdMejQis
(3cJHJ HYV GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs